New nematode-resistant potato varieties - Borzykh, O.; Taktaev, B.; Pisarenko, N.; Podberezko, I.; Sigaryova, D.; Bondar , T. (Quarantine and plant protection, 2023)
Goal. Creation of new varieties of potatoes of different groups of ripeness, table use, high productivity, increased level of starch and good taste qualities, resistant to the golden cyst-forming nematode, common and aggressive pathotypes of cancer, fungal and bacterial diseases. Methods. Selection work was carried out in accordance with the generally accepted scheme of the selection process. The resistance of breeding material against Globodera rostochiensis was evaluated in accordance with the «Regulations on the Procedure for Testing Potato Varieties and Hybrids». Results. The 12 best hybrids — Zlagoda, Myroslava, Knyaginya, Vzyrets, Bazaliya, Opillya, Bazhana, Fanatka, Avangard, Predslava, Oleksandrite and Rostavitsa — were selected and submitted to the State Trial as varieties. Of the 12 transferred varieties, 11 (Zlagoda, Myro slava, Knyaginya, Vzyrets, Bazaliya, Opillya, Avangard, Predslava, Oleksandrit, Fanatka, Rostavitsa) successfully passed the State variety test in 2023 and were entered into the State Register of plant varieties suitable for distribution in Ukraine. Conclusions. The new 11 varieties included in the State Register of plant varieties suitable for distribution in Ukraine are advisable to use as a means of controlling the harmfulness of the golden potato nematode in areas infected with Globodera rostochiensis (pathotype Ro1).